YouTube Video in Improving Senior High Students’ Vocabulary Mastery - Nurfadilla; Andi Rachmawati; Faridawati; Syahriani (Institut Agama Islam Negeri Palopo, 2024)
The study aims to investigate the practical implications of using YouTube videos to improve the vocabulary mastery ability of students in class X RPL B (Rekayasa Perangkat Lunak) SMK Negeri 4 Kendari. The researcher used a pre-experimental research method using one group pre-test and post-test design. The sample of this study was 30 class X students from the RPL B (Rekayasa Perangkat Lunak) department of SMK Negeri 4 Kendari. The data collection instruments used in this study were pre-test and post-test. Based on the results of the data analysis, the average pre-test score was higher than the post-test, with a pre-test of 54.78 and a post-test of 81.44. Based on the results of statistical calculations using paired sample t-test, the standard deviation value was 10.47 with a significance level of 0.000. Thus, it can be assumed that H₁ is accepted, which indicates a significant increase in students' comprehension ability before and after learning using YouTube videos. Therefore, it can be concluded that the application of YouTube videos effectively improves the comprehension ability of class X RPL B students of SMK Negeri 4 Kendari in the 2023/2024 academic year, providing practical insights for language educators and stakeholders.